2020
DOI: 10.1038/s41598-020-78817-x
|View full text |Cite
|
Sign up to set email alerts
|

(R)-Roscovitine and CFTR modulators enhance killing of multi-drug resistant Burkholderia cenocepacia by cystic fibrosis macrophages

Abstract: Cystic fibrosis (CF) is characterized by chronic bacterial infections and heightened inflammation. Widespread ineffective antibiotic use has led to increased isolation of drug resistant bacterial strains from respiratory samples. (R)-roscovitine (Seliciclib) is a unique drug that has many benefits in CF studies. We sought to determine roscovitine’s impact on macrophage function and killing of multi-drug resistant bacteria. Human blood monocytes were isolated from CF (F508del/F508del) and non-CF persons and der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Mabs infections are associated with severe pneumonia and accelerated inflammatory lung damage in CF patients 70,71 . In line with results previously obtained 31,32 , Roscovitine reduces intracellular bacterial loads in both WT and CF macrophages infected with Mabs, likely by enhancing their ability to kill bacteria. As intracellular bacterial destruction by professional phagocytes is crucial to control Mabs infection 6,72 , perhaps stimulating antibacterial activity using Roscovitine and thereby precluding the establishment of an acute infection could be a therapeutic strategy in CF-related Mabs infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mabs infections are associated with severe pneumonia and accelerated inflammatory lung damage in CF patients 70,71 . In line with results previously obtained 31,32 , Roscovitine reduces intracellular bacterial loads in both WT and CF macrophages infected with Mabs, likely by enhancing their ability to kill bacteria. As intracellular bacterial destruction by professional phagocytes is crucial to control Mabs infection 6,72 , perhaps stimulating antibacterial activity using Roscovitine and thereby precluding the establishment of an acute infection could be a therapeutic strategy in CF-related Mabs infection.…”
Section: Discussionsupporting
confidence: 91%
“…As intracellular bacterial destruction by professional phagocytes is crucial to control Mabs infection 6,72 , perhaps stimulating antibacterial activity using Roscovitine and thereby precluding the establishment of an acute infection could be a therapeutic strategy in CF-related Mabs infection. Roscovitine stimulates macrophage bactericidal activity by restoring intra-phagolysosome acidic pH 31,32 (which is abnormally high in CF macrophages 73 ). Having shown that professional phagocytes acidify phagosomes to efficiently control Mabs 72,74,75 , Roscovitine-mediated intra-phagosomal acidification could account for the Mabs infection phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules generally act by impairing bacterial growth, permeabilizing bacteria through the alteration of the structure of the outer membrane, inhibiting biofilm formation and eradicating established biofilms [114,116]. Alternative approaches based on molecules used for other diseases, natural products, quorum-sensing inhibitors and antimicrobial peptides are under investigation [118][119][120][121]. Finally, interest in the design of B. cenocepacia vaccines has recently risen [122].…”
Section: Rnd In Burkholderia Cenocepaciamentioning
confidence: 99%
“…The different behavior of Orkambi® and Symdeko® unveils a novel anti-inflammatory property exclusive to coadministration of tezacaftor, which may thus exert a wide range of therapeutic effects against lung infection and inflammation, both associated with IL-1β. Furthermore, very recent results from Shrestha and colleagues identified a synergistic effect between R-roscovitine, a synthetic tri-substituted purine that has shown multiple benefits in CF [48,49], and Symdeko® in the killing of Burkholderia cenocepacia by CF macrophages [118], thus disclosing new encouraging perspectives on the use of the tezacaftor/ivacaftor combination to dampen CF inflammation.…”
Section: Combination Therapies: Orkambi® and Symdeko®mentioning
confidence: 99%